Aplikasi statistika dalam menentukan nilai karakteristik tanah: sebuah studi pustaka - Budhi Setiawan (Indonesian Journal on Geoscience, 2008)
http://dx.doi.org/10.17014/ijog.vol3no2.20083In this paper, determination of characteristic value of soil properties based on a statistical method is explained. The value in the limit state design is not the point value as measured by a laboratory or field test. Two confusing concepts in statistical soil mechanics are: the modeling of variability by a random field model and the distinction between the population mean and sample mean. Intrinsically, these two concepts are related to each others. The paper demonstrates that the most confusing thing what is being dilemmas in determining soil characteristic value may be removed by considering a statistical method.